Pengaruh Perawatan Luka Modern Dressing Terhadap Derajat Luka Ulkus Diabetikum - Sartika, Andry; Ferasinta, Ferasinta; Novitasari, Selvia; Rozani, Leni (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
One of the complications of Diabetes Mellitus (DM) is Diabetic Ulcer. Diabetic ulcers are wounds that require special care, management to treat diabetic ulcers, namely the Modern Dressing method. Diabetic foot wounds are caused by several factors, namely neuropathy, trauma, foot deformity, high pressure on the soles of the feet and peripheral vascular disease. Comprehensive and systemic examination and classification of diabetic ulcers can help provide and guide adequate treatment. The aim of this study was to determine the effect of wound care using modern dressing methods on the degree of diabetic ulcers. This research uses a quasi-experimental method with a pre-post test two group design approach, namely a research method carried out observationally. The research results showed that the average value of wound care using modern dressing methods was the average value before (19.15) and the average after intervention (12.81). So it can be said that there is an influence of modern dressings on the degree of diabetic ulcer wounds.